Implementasi Fasilitas Sekolah Pada SMA Se-Medan - Sayyidati Maliha; Mahdia Arafah; Rizazah Putri Raudina; Putri Malika Alya; Deasy Yunita Siregar (Jurnal Bima : Pusat Publikasi Ilmu Pendidikan Bahasa dan Sastra, 2024)
Implementing a schoolfacilities is a management plan to manage and maintain educational institutions such as schools, academies and multi-academy trusts can be an overwhelming task. However, having an effective facility management system such as facility management software and also hardware can provide several benefits. For example, improving learning environments, improving school quality and quantity and supporting the educational outcomes of every student. If almost 50% of teachers believe that their workplace harms their well-being, it is worth thinking about how the introduction of a commercial venue and facility could help.